2018
DOI: 10.1002/jnr.24226
|View full text |Cite
|
Sign up to set email alerts
|

Citalopram attenuated neurobehavioral, biochemical, and metabolic alterations in transient middle cerebral artery occlusion model of stroke in male Wistar rats

Abstract: Oxidative stress and inflammation are implicated as cardinal mechanisms of neuronal death following stroke. In the present study citalopram (Cit) was investigated in a 2 h middle cerebral artery occlusion (MCAo) model of stroke in male Wistar rats. Pretreatment, posttreatment (Post Cit) and pre plus posttreatment (Pre + Post Cit) with Cit were evaluated for its neuroprotective effect. In pretreatment protocol, effect of Cit at three doses (2, 4, and 8 mg/kg) administered i.p., 1 h prior to MCAo was evaluated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…These outcomes are supported by the findings of Gupta et al. (2018). They expounded the neuroprotective role of citalopram (2, 4, and 8 mg/kg) in Wistar rats and observed the antioxidant mechanism behind the neuroprotective action of citalopram.…”
Section: Discussionsupporting
confidence: 85%
“…These outcomes are supported by the findings of Gupta et al. (2018). They expounded the neuroprotective role of citalopram (2, 4, and 8 mg/kg) in Wistar rats and observed the antioxidant mechanism behind the neuroprotective action of citalopram.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, Fluoxetine injections in rat models enhanced neurogenesis and prevented a pathological increase in stem cell recruitment in the hippocampus [228]. Similarly, Citalopram demonstrates neuroprotective effects by decreasing oxidative stress, inflammation and apoptosis [229]. Additionally, the natural antidepressant hyperforin also improves post-stroke depression and post-stroke isolation in rat models by inhibiting TGF-β resulting in the promotion of hippocampal neurogenesis [230,231].…”
Section: Anti-inflammatory Properties Of Antidepressantsmentioning
confidence: 99%
“…Citalopram exerted anti-inflammatory and antioxidant activities in a rat model of focal cerebral ischemia. Pre, post and pre and post administration of it reduced cerebral infarct volume, grip test score and neurological deficit score in a 2 h MCAO model of ischemia [55]. Another study showed that citalopram protected CA1 pyramidal cells after transient cerebral ischemia in gerbil through prevention of excitatory amino acids, glutamate and aspartate, accumulation during and after forebrain ischemia [56] and also decreased glutamate release from lipopolysaccharideactivated microglia which in turn increased the survival of oxygen-glucose deprivation injured neurons [57].…”
Section: Citaloprammentioning
confidence: 99%
“…Citalopram alleviates the activity of the apoptotic markers, caspase-3, caspase-9, MMP-2 and MMP-9 and reduces the levels of MDA and NO. It reduces the release of the inflammatory mediators; TNF-α and IL-1β which ameliorate the ischemia-induced cell death and inflammation [55][56][57]. As fluoxetine and paroxetine, escitalopram overexpresses BDNF and reduces ischemiainduced oxidative stress.…”
Section: Proposed Mechanisms Of the Neuroprotective Role Of Ssris And Snris In Cerebral Ischemiamentioning
confidence: 99%